Pendidikan Budaya;Di Sekolah dan Komunitas/Masyarakat - Rusdiansyah Rusdiansyah (Institut Agama Islam Negeri Palopo, 2020)
The aims of this paper is to see how education and culture are related and mutually supportive in order to achieve the goals of education. This research is a library research using a descriptive analysis method. Education aims to shape so that humans can demonstrate their behavior as cultured beings who are able to socialize in their communities and adapt to their environment in an effort to maintain survival, both individually, in groups, and society as a whole. Cultural approach is the right way in fostering the morality of the nation's education which began to collapse, this is because culture contains various aspects, such as religion, ethics and the environment. Through a cultural approach, we can instill positive values so that students are able to become human beings who have character, humans who can accompany their activities with existing norms or values.